QUASI-GEOSTROPHIC KINEMATIC DYNAMOS AT LOW MAGNETIC PRANDTL NUMBER - Schaeffer N.; Cardin P. (My University, 2006)
Rapidly rotating spherical kinematic dynamos at very low Ekman and Prandtl numbers are computed using the combination of a quasi-geostrophic (QG) model for the velocity field and a classical spectral 3D code for the magnetic field. The QG flow is computed in the equatorial plane of the sphere; it corresponds to Rossby wave instabilities of a geostrophic internal shear layer produced by differential rotation. The induction equation is computed in the whole sphere after the QG flow has been expanded along the rotation axis. Differential rotation and Rossby wave propagation are the key ingredients of this dynamo which can be interpreted in terms of Parker-Ω dynamo. Taking into account the quasi-geostrophy of the velocity field enables us to increase time and space resolution to compute the dynamics. For the first time, we report on numerical dynamos with very low Ekman numbers (10- 8). Because the magnetic and velocity fields are computed on different grids, we compute dynamos for very low magnetic Prandtl numbers exhibiting a scale separation between magnetic and velocity field. These dynamos are asymptotically close to rapidly rotating, metallic planetary cores. © 2006 Elsevier B.V. All rights reserved.
Keywords: GEODYNAMO; GEOSTROPHY; KINEMATIC DYNAMOS; MAGNETIC FIELDS; QUASI-GEOSTROPHIC MODEL; SCALE SEPARATION